2020
DOI: 10.1021/acsami.0c03040
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Loaded Quatsomes Exhibiting FRET as Nanoprobes for Bioimaging

Abstract: Fluorescent organic nanoparticles (FONs) are emerging as an attractive alternative to the well-established fluorescent inorganic nanoparticles or small organic dyes. Their proper design allows one to obtain biocompatible probes with superior brightness and high photostability, although usually affected by low colloidal stability. Herein, we present a type of FONs with outstanding photophysical and physicochemical properties in-line with the stringent requirements for biomedical applications. These FONs are bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Finally, the cellular penetration capability of different types of fluorescent QSs in different cell lines has been also reported. [32][33][34][35] In this respect, introducing responsiveness to external molecular inputs within fluorescent QS nanovesicle could pave the way for the rational design of multifunctional biomimetic vesicles capable of translating the recognition of target molecules into signal transduction for biosensing applications. Motivated by the above considerations, here we anchor fluorescent cholesterol-modified DNA probes (i.e., F-miRNA probe) on dye-loaded QSs, to produce FRET-active nanovesicles responsive to clinically relevant nucleic acid targets such as microRNAs (miRNA), a class of small endogenous non-coding RNAs that can be used as diagnostic and prognostic markers in multiple human diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the cellular penetration capability of different types of fluorescent QSs in different cell lines has been also reported. [32][33][34][35] In this respect, introducing responsiveness to external molecular inputs within fluorescent QS nanovesicle could pave the way for the rational design of multifunctional biomimetic vesicles capable of translating the recognition of target molecules into signal transduction for biosensing applications. Motivated by the above considerations, here we anchor fluorescent cholesterol-modified DNA probes (i.e., F-miRNA probe) on dye-loaded QSs, to produce FRET-active nanovesicles responsive to clinically relevant nucleic acid targets such as microRNAs (miRNA), a class of small endogenous non-coding RNAs that can be used as diagnostic and prognostic markers in multiple human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Their high stability, that is, also in body fluids, [31] unilamellarity and particle-to-particle homogeneity make them an attractive soft material for sensing applications. Furthermore, we recently demonstrated the possibility to confine hundreds of organic dyes in a single QS [32][33][34] and even the simultaneous loading of a Förster resonance energy transfer (FRET) dye pair in QSs yielding ultra-bright nanovesicles, whose brightness compares with the most common quantum dots, [35] enabling their use for molecular detection and imaging. Finally, the cellular penetration capability of different types of fluorescent QSs in different cell lines has been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Absorption spectra revealed that nanovesicles either in liquid dispersion or in gel maintain DiI and DiD molecules in the nanovesicles nanostructure since no change in the main absorption bands (Abs(DiI) = 551 nm and Abs(DiD) = 650 nm) are observed. It is worth noting that DiD is prone to form aggregates such as H-dimers, generally reported by an increase in the absorption shoulder at 600 nm [58,64]. However, spectra displayed in Figure 7b point out the lack of those aggregates or any other non-monomeric forms of DiD.…”
Section: Integrity Of Delos Nanovesicles When Gellifiedmentioning
confidence: 83%
“…The integration of dyes in similar DELOS nanovesicles dispersed in water as one of the selected media has been widely studied by N. Ventosa and collaborators [57]. Previously, vesicles with 1,1 -dioctadecyl-3,3,3 ,3tetramethyl-indocarbocyanine perchlorate (DiI) and 1,1 -dioctadecyl-3,3,3 ,3 -tetramethylindodicarbocyanine perchlorate (DiD) fluorophores were successfully prepared [58]. Importantly, DiI and DiD is a well-known Fluorescence Resonance Energy Transfer (FRET) pair [59][60][61], thus, when those dyes are nearby (typically <10 nm) they experiment high FRET efficiencies, providing information about the distance between both fluorophores.…”
Section: Integrity Of Delos Nanovesicles When Gellifiedmentioning
confidence: 99%
“…The pathways for energy transfer between fluorescent substances can be divided into radiant energy transfer and nonradiative energy transfer. Fluorescence resonance energy transfer is a nonradiative energy transfer process [10,58] . This type of energy transfer can occur between different molecules and different chromophores of the same molecule.…”
Section: Biological Applications Related To Rtcsmentioning
confidence: 99%